Uniqueness of Meromorphic Functions Sharing a Certain Nonzero Polynomial With Weight - Majumder, Sujoy (Sarajevo Journal of Mathematics, 2024)
In this paper we investigate the uniqueness problem of meromorphic functions when certain non-linear differential polynomials share a nonzero polynomial. We prove a uniqueness result which significantly rectify, improves and generalizes the recent results of P. Sahoo and S. Seikh as well as X. M. Li and L. Cao.